Diagnostic and therapeutic treatment modalities for acute lower gastrointestinal bleeding: a systematic review. - Oakland, K; Isherwood, J; Lahiff, C; Goldsmith, P; Desborough, M; Colman, K; Guy, R; Uberoi, R; Murphy, M; East, J; Hopewell, S; Jairath, V (Thieme Open, 2017)
Investigations for lower gastrointestinal bleeding (LGIB) include flexible sigmoidoscopy, colonoscopy, computed tomographic angiography (CTA), and angiography. All may be used to direct endoscopic, radiological or surgical treatment, although their optimal use is unknown. The aims of this study were to determine the diagnostic and therapeutic yields of endoscopy, CTA, and angiography for managing LGIB, and their influence on rebleeding, transfusion, and hospital stay. A systematic search of MEDLINE, PubMed, EMBASE, and CENTRAL was undertaken to identify randomized controlled trials (RCTs) and nonrandomized studies of intervention (NRSIs) published between 2000 and 12 November 2015 in patients hospitalized with LGIB. Separate meta-analyses were conducted, presented as pooled odds (ORs) or risk ratios (RR) with 95 % confidence intervals (CIs). Two RCTs and 13 NRSIs were included, none of which examined flexible sigmoidoscopy, or compared endotherapy with embolization, or investigated the timing of CTA or angiography. Two NRSIs (57 - 223 participants) comparing colonoscopy and CTA were of insufficient quality for synthesis but showed no difference in diagnostic yields between the two interventions. One RCT and 4 NRSIs (779 participants) compared early colonoscopy (< 24 hours) with colonoscopy performed later; meta-analysis of the NRSIs demonstrated higher diagnostic and therapeutic yields with early colonoscopy (OR 1.86, 95 %CI 1.12 to 2.86, P  = 0.004 and OR 3.08, 95 %CI 1.93 to 4.90, P  < 0.001, respectively) and reduced length of stay (mean difference 2.64 days, 95 %CI 1.54 to 3.73), but no difference in transfusion or rebleeding. In LGIB there is a paucity of high-quality evidence, although the limited studies on the timing of colonoscopy suggest increased rates of diagnosis and therapy with early colonoscopy.